Factors Related to Income Change among Elderly: Dynamics of Poverty Based on a Longitudinal Survey - KOBAYASHI, Erika; HARADA, Ken; LIANG, Jersey; SUGISAWA, Hidehiro (Japanese Sociological Review, 2001)
Based on a longitudinal survey (1987-1990) of a national representative sample aged 60 and over, we examined the income change rate of elderly and the factors related to their movement into and out of poverty. A couple is defined as poor if their annual income is less than 1.2 million yen. Independent variables such as socioeconomic status and life event indicators are taken into account. The findings are as follows : 1. The poverty rate was 34.7% in 1987, and 31.7% in 1990. Comparing baseline and follow-up interviews, 8.8% of the sample experienced a fall into poverty, while 11.8% moved out of it. 2. Socioeconomic status showed differences in the likelihood of a subject's moving into or out of poverty. Interviewees who had higher educational attainment were less likely to become poor, and the longest-held occupation had significant effects on the likelihood of a subject's moving into or out of poverty. 3. During the period of the survey, life events were found to have significant effects on the likelihood of moving into or out of poverty. Women who became widowed and subjects who became unemployed were more likely to move into poverty, while those who continued to be employed were more likely to move out of poverty. 4. Sex, age and functional capacity had significant effects on the likelihood of moving out of poverty even after the effects of socioeconomic status and life events were controlled. Men were more likely to move out of poverty than women were, while subjects who were older and subjects who had a lower functional capacity at the baseline were less likely to do so.